A Design of Gain Boosted Error Amplifier Applied to PWM Control - Yu Shi-Hua; Wang Kai-Yu; Wei Shu-Ping; Wang Xiao-Feng; Yang Ming-Jian (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A high gain, wide common-mode and high swing error amplifier is proposed. It can be applied to a PWM control chip. The error amplifier adopts folded cascode structure with gain boosted. This chip is simulated and fabricated in the CSMC 0.5μm CMOS. The result shows that the error amplifier has the DC gain of 141.11dB, the common-mode input range of 0~3.87v and the output swing of 0.11~4.80v. These meet the requirements of engineering applications and can realize stable system output. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2461